Returns to On-the-Job Soft Skills Training - Adhvaryu, Achyuta; Kala, Namrata; Nyshadham, Anant (Journal of Political Economy, 2023)
We estimate productivity gains of 13.5% from workplace soft skills training among Indian garment workers. Productivity gains are greater when trainees work on joint operations alongside other coworkers, consistent with gains being driven by improved teamwork and collaboration. Furthermore, untreated coworkers on the treated production lines also show increased productivity. These improvements in the teamwork substitute for managerial attention. Despite productivity gains and higher promotion probabilities among treated workers, there are no effects on wages or retention, consistent with frictions in this labor market. Consequently, the net return to the firm was large: 256% 8 months after program completion.